Parallels in Development of Modern Painting and Enameling in China - Daria Mostovshchykova; Nataliia Stryzhko (ITB Journal Publisher, LPPM ITB, 2021)
This paper highlights trends in the development of contemporary visual art in China through a parallel analysis of two of its components: painting and enamel art. The focus of the research is on the work of artists whose works combine a ‘western’ style with ‘eastern’ tradition. It was found that in the 21st century, the layer of Chinese cultural heritage was successfully transformed into new forms of expression, such as art objects, enamel sculptures, brightly colored paintings and more. At the same time, it has preserved the symbolism of color, plasticity of lines, narrative and figurative components, which is typical of the centuries-old traditions of the Celestial Empire. Artistic analysis was carried out on specific pictorial and enamel examples, distinguishing common and distinctive features in the concepts of the artists and their embodiment in the material. The way in which contemporary art enters the urban space of megacities and the interior of public institutions was analyzed. In conclusion, it is emphasized that the combination of ‘traditional’ and ‘recent’ trends in one work help to rethink the role of classical images in today’s art, as well as to identify Chinese artists in the globalized intercultural space.